Nickel induced exposure analysis for toxic changes in growth and antioxidative enzymes in sesban eliciting biochemical sensitivity - Mania, S; Mohanty, M (Plant Science Today, 2025)
Nickel (Ni) exposure in plants leads to severe toxicity problems, with effects varying depending on its exposure concentration. The present pot culture investigation assesses the phytotoxic effects of different Nickel (Ni) concentrations on various biochemical parameters of Sesbania. The study involves applying Nickel at 50, 100, 200, and 300 ppm along with a control group at 0 ppm for 30 days. Results revealed retarded growth, reduced pigment content, and enhanced antioxidative enzyme activity as nickel concentration increased. Exposure to Ni (100 ppm) and above severely affects seed germination, plant growth, and biomass production. Furthermore, relative phytotoxicity was evident from a 15% reduced germination rate and a fall in germination index from 10 to 8.5. The seedling vigour index was drastically reduced from 960 (control) to 93.5(300 ppm Ni). In addition to these, plant growth retardation was striking with root length stunted by 70% and shoot length by 50% in response to Ni (300 ppm). Chlorophyll and carotenoid contents decreased by nearly 50% with the 300-ppm nickel treatment. Although protein levels and antioxidant enzyme activity (catalase and peroxidase) showed a stimulatory response to 100 and 200 ppm Ni treatments, both suffered a sharp decline due to toxic stress at 300 ppm Ni. This study explicitly highlights the harmful effects of high doses of Ni, highlighting the sensitivity of various morphometric and biochemical parameters to Ni toxicity. These findings highlights the need to mitigate environmental contamination and adopt measures to protect plant health.